Are all RAS mutations the same? Coexisting KRAS and NRAS mutations in a caecal adenocarcinoma and contiguous tubulovillous adenoma. Issue 8 (29th April 2015) - Vagaja, N N; Parry, J; McCallum, D; Thomas, M A; Bentel, J M
Abstract : Mutations of the human Kirsten rat sarcoma viral oncogene homologue ( KRAS ) and the highly homologous human neuroblastoma RAS viral oncogene homologue ( NRAS ) are associated with resistance to antiepidermal growth factor receptor therapies in patients with colorectal cancer. In this report, we describe a caecal adenocarcinoma that contains both KRAS c.35G>T (G12V) and NRAS c.34G>A (G12S) mutations. The adenocarcinoma arises from a contiguous high-grade tubulovillous adenoma, which also carries the identical KRAS and NRAS mutations, supporting their common origin. While KRAS mutations are common in colorectal cancers, NRAS mutations are relatively rare and the coexistence of multiple RAS mutations is not documented, presumably reflecting similar functions of wild-type and mutant forms of RAS. Recent experimental evidence has suggested that KRAS and NRAS may in fact mediate distinct biological processes in the colon, and this unusual case potentially illustrates the hypothesis clinically. Characterisation of the diverse and divergent functions of RAS family members and mutant forms of RAS in the colon form important considerations for the development of RAS-targeting therapeutics.